1988
DOI: 10.1152/jappl.1988.65.5.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects on respiratory pattern of focal cooling in the medulla of the dog

Abstract: Studies in cats have shown that, in addition to respiratory neuron groups in the dorsomedial (DRG) and ventrolateral (VRG) medulla, neural structures in the most ventral medullary regions are important for the maintenance of respiratory rhythm. The purpose of this study was to determine whether a similar superficially located ventral region was present in the dog and to assess the role of each of the other regions in the canine medulla important in the control of breathing, in 20 anesthetized, vagotomized, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…century Wang, 1980 , and the region around the ventral Ž . respiratory group VRG of the medulla has been found to Ž be the site most important for such action Adams et al, 1988;Feldman and Smith, 1989;Onimaru et al, 1989;. Onimaru, 1995;Paton et al, 1994 . We have observed that Ž .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…century Wang, 1980 , and the region around the ventral Ž . respiratory group VRG of the medulla has been found to Ž be the site most important for such action Adams et al, 1988;Feldman and Smith, 1989;Onimaru et al, 1989;. Onimaru, 1995;Paton et al, 1994 . We have observed that Ž .…”
Section: Introductionmentioning
confidence: 88%
“…Ž . Adams et al 1988 reported that in dogs, insertion of a cryoprobe needle into the ventral and dorsal respiratory group for cooling the medulla often produced respiratory distress.…”
Section: Mechanical-minute Lesion In Vrg-apa May Cause Apneamentioning
confidence: 99%